OFR-3(6)-75 Design And Development Of Protective Canopies For Underground Low Coal Electric Face Equipment, Including Shuttle Cars - Installation And Maintenance Manual: Protective Canopy For Galis Mfg. Co. Roof Drill ? 1. Introduction (The National Institute for Occupational Safety and Health (NIOSH), 1973)
This manual provides instructions for installing, operating, and maintaining a protective canopy on the Galis Mfg. Co. roof drill. The instructions are based upon two actual installations: one made in a mine on roof drill, model 300, and one in the factory. The parts list and engineering drawings for the protective canopy are included at the end of the manual. And a discussion of some alternative design concepts is also included. The manual can also be used for retrofitting other roof drills with similar protective canopies. Skilled mechanics can determine if the instructions herein would be applicable to the other roof drills and can determine any necessary modifications if they are not.